Rest in pizza - Cavender, Chris (Cavender, Chris. Pizza lovers mystery., 2012)
"Cozy towns like Timber Ridge, North Carolina-the home of Eleanor Swift's delectable pizzeria, A Slice of Delight-don't take well to prima donna celebrities. So no one is particularly pleased when TV host and famous chef Antonio Benet roars into town for a book signing and manages to insult Eleanor, her deliciously saucy sister Maddie, and everyone else within earshot. Insults are one thing, however...but a cold dish of murder is quite another."--Dust jacket.